The nexus between governance quality and economic growth of Malaysia: Short- and long-run analyses - Saizal Pinjaman; Mohamad Afifi Mat Thani; Syamsul Hadi; Mohd. Allif Anwar Abu Bakar (IDEAS, 2025)
This study investigates the impact of governance quality on Malaysia’s economic growth from 2000 to 2021, focusing on six World Governance Indicators (WGI): voice and accountability, political stability, government effectiveness, regulatory quality, rule of law, and control of corruption. Despite Malaysia’s significant economic progress, the relationship between governance quality and growth remains underexplored, particularly in terms of long-run and short-run dynamics. Using the cointegration and error correction models, the study examines the short-run and long-run relationships between governance indicators and real GDP. The findings reveal that political stability and government effectiveness have significant positive long-run impacts on real GDP, emphasizing their critical role in fostering economic growth. However, regulatory quality and rule of law, while positively correlated, are statistically insignificant in the long run, suggesting that their benefits may take longer to materialize. Control of corruption shows a counterintuitive negative long-run relationship, likely due to transitional costs of anti-corruption measures. In the short run, most governance indicators significantly influence real GDP, with the error correction term confirming a robust adjustment toward long-run equilibrium. The study recommends prioritizing political stability and government effectiveness while implementing sustained reforms to enhance regulatory quality, rule of law, and anticorruption measures. Policymakers should adopt a holistic approach to governance reforms, ensuring transparency, accountability, and institutional efficiency to support Malaysia’s long-term economic growth and resilience. These insights are crucial for aligning governance strategies with Malaysia’s development goals under initiatives like the Shared Prosperity Vision 2030.